Relative income, happiness and utility: an explanation for the Easterlin paradox and other puzzles - Andrew E. Clark; Paul Frijters; Michael A. Shields (Institute for the Study of Labor (IZA), 2007)
The well-known Easterlin paradox points out that average happiness has remained constant over time despite sharp rises in GNP per head. At the same time, a micro literature has typically found positive correlations between individual income and individual measures of subjective well-being. This paper suggests that these two findings are consistent with the presence of relative income terms in the utility function. Income may be evaluated relative to others (social comparison) or to oneself in the past (habituation). We review the evidence on relative income from the subjective well-being literature. We also discuss the relation (or not) between happiness and utility and discuss some non-happiness research (behavioural, experimental, neurological) dealing with income comparisons. We last consider how relative income in the utility function affects economic models of behaviour in a number of different domains.
Keywords: 330; Lebenszufriedenheit; Sozialprodukt; Einkommensverteilung; Interpersoneller Nutzenvergleich; Theorie; Welt